2010
DOI: 10.1038/oby.2009.155
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss, HbA1c Reduction, and Tolerability of Cetilistat in a Randomized, Placebo‐controlled Phase 2 Trial in Obese Diabetics: Comparison With Orlistat (Xenical)

Abstract: IntroductIonWeight control plays an important role in the management of patients with type 2 diabetes and is typically addressed by lifestyle modifications. These focus on a nutritionally balanced, moderately hypocaloric diet, with a reduced intake of saturated fat and an increase in physical activity (1-6). Current pharmacological options for weight management are limited, with only three agents, orlistat (an inhibitor of gastric and pancreatic lipases) (7-10), sibutramine (a combined reuptake inhibitor of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 18 publications
(21 reference statements)
1
44
0
8
Order By: Relevance
“…51,55 The remaining 12 studies (2 studies were single-group pre-post designs, 1 study had a more active comparison group, and 9 studies reported outcomes at < 12 mo) were only included in analyses of adverse events. 24,29,57,63,[75][76][77][78][79][80][81]83 High within-group heterogeneity was common; however, the direction of treatment effect was consistent across most studies, and the confidence intervals overlapped. This statistical heterogeneity is likely due to small versus large treatment effects observed across studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51,55 The remaining 12 studies (2 studies were single-group pre-post designs, 1 study had a more active comparison group, and 9 studies reported outcomes at < 12 mo) were only included in analyses of adverse events. 24,29,57,63,[75][76][77][78][79][80][81]83 High within-group heterogeneity was common; however, the direction of treatment effect was consistent across most studies, and the confidence intervals overlapped. This statistical heterogeneity is likely due to small versus large treatment effects observed across studies.…”
Section: Resultsmentioning
confidence: 99%
“…20,27,57,59,61,66,67,[70][71][72][73]77,79,84 Gastrointestinal events were reported only in studies that used drug interventions and in the 23 studies with data that could be pooled; those taking active medications were more likely to report these events than control participants. 57,59,[61][62][63][64][65][66][67][68][69][71][72][73][74][75][76][77]79,[81][82][83][84] Likewise, participants in 25 pharmacologic studies were more likely to withdraw from their study because of adverse events compared with control participants (Table 5). 46,56,[58][59][60][61][62][63][64][65]…”
Section: Cmaj Openmentioning
confidence: 99%
“…It has not been launched in Japan, but is being sold by an Indian company [9]. It has similar efficacy to orlistat, but is claimed to show a reduced incidence of gastrointestinal side-effects [10,11].…”
Section: Disappointments Past and Presentmentioning
confidence: 99%
“…20 The adverse side effects of cetilistat are similar to those reported with orlistat, although such events were less frequent, suggesting better tolerability and therefore compliance. 20,21 Liraglutide is a glucagon-like peptide-1 (GLP-1) analogue of the endogenous gut-derived hormone incretin. It is already known to improve glycosylated haemoglobin concentrations, beta cell function and systolic blood pressure.…”
Section: Combination Therapymentioning
confidence: 99%